Розробка та відпрацювання методики введення в культуру in vitro рослин міскантусу - Мельничук, О.В.; Ожерєдов, С.П.; Секан, А.С.; Баєр, Г.Я.; Шиша, О.М.; Емець, А.І. (Фактори експериментальної еволюції організмів, 2015)
Aims. Miscanthus is one of the most promising plant species for the second generation technologies of biofuel production. Main advantages of Miscanthus are its high vegetative mass with significant content of cellulose, especially in the case of M. giganteus, where this parameter exceeds 70 %. Establishment of miscanthus in vitro culture has some difficulties due to high contamination rate of explants, especially if the latter are from underground part of plants. This problem was reported by several authors. The aim of the study was to develop an efficient protocol for root adventitious buds sterilization in three Miscanthus species, namely, M. sinensis, M. sacchariflorus and M. giganteus. Methods. Root adventitious buds were used as explants for establishment of in vitro culture. For sterilization several compounds at different concentrations and different exposure time were tested, sodium hypochlorite (NaOCl) at different concentrations and silver nitrate (AgNO3 ) at concentrations 0.02 and 0.04 % among them. In addition, 0.15 % fungicide (previcur) and 250 mg/l of antibiotic (cefotaxime) were present in sterilization solution. Dry sterilization with gas (Cl2 ) was tested as well. Results. The lowest contamination rate was observed when explants were sterilized in 0.04 % solution of AgNO3 , less efficient yet satisfactory results were obtained after sterilization in 9 % NaOCl solution. Conclusions. Application of efficient sterilization protocols allows us to establish in vitro culture for all of three Miscanthus species tested in the experiment and to use root adventitious buds as explants. Keywords: surface sterilization, explants, tissue culture, Miscantus, in vitro culture, establishment, root adventitious buds.